Ijbar Nikah di Kampung Sidosermo Dalam Surabaya Perspektif Hukum Islam - Argo, Abdulloh Faqih Putro; Amin, Mokhammad Rizky Khoirul; Nurkholis, Muh; Rouf , Abdul; Musyafa’ah, Nur Lailatul (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2020)
This article discusses about the forced marriage in Sidosermo Dalam Surabaya to be analyzed by Islamic law. This research is field research and is qualitative in nature. Data were collected through interviews and documentation, then analyzed deductively. The forced marriage still occurs in Sidosermo Dalam Surabaya. Marriage was motivated by several reasons: the factor of parents' concern for their child, the factor of family relations, the existence of myths, the existence of Syafii's understanding of fiqh that allows the forced marriage, and economic factors. The forced marriage can occur in girls and boys even though they are adults. In Islamic law, all schools of thought think that the permissible marriage permit is for girls who are not yet mature, while for those who are adults or who are widows there is a dispute between the imam of the mazhab. In the KHI, the forced marriage should not occur because the marriage can be carried out with the consent of the two prospective brides. [Artikel ini membahas tentang ijbar nikah di Sidosermo Dalam Surabaya untuk dianalisis dengan hukum Islam. Penelitian ini adalah penelitian lapangan dan bersifat kualitatif. Data dikumpulkan melalui wawancara dan dokumentasi, kemudian dianalisis secara deduktif. Ijbar nikah masih terjadi secara masif di Kampung Sidosermo Dalam Surabaya. Perkawinan itu dilatarbelakangi oleh beberapa sebab, yaitu faktor kekhawatiran orang tua terhadap anaknya, faktor hubungan keluarga, adanya mitos, dan adanya pemahaman fikih Syafii yang membolehkan ijbar nikah. Ijbar nikah tersebut bisa terjadi pada anak perempuan dan laki-laki meski sudah dewasa. Dalam hukum Islam, semua mazhab berpendapat bahwa ijbar nikah yang diperkenankan adalah kepada anak perempuan yang belum dewasa, sedangkan yang sudah dewasa atau yang janda terdapat perselisihan di antara imam mazhab. Dalam KHI, ijbar nikah tidak semestinya terjadi karena pernikahan bisa dilakukan dengan persetujuan dari kedua calon mempelai.]